2017
DOI: 10.1103/physrevd.96.075046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of LHC data on muon g2 solutions in a vectorlike extension of the constrained MSSM

Abstract: Abstract:The long-standing discrepancy between the experimental determination by the Muon g − 2 Collaboration at Brookhaven and the Standard Model predictions for the anomalous magnetic moment of the muon cannot be explained within simple unified framework like the Constrained Minimal Supersymmetric Standard Model, but it can within its extension with vector-like fermions. In this paper we consider a model with an additional vector-like 5 +5 pair of SU (5). Within this model we first identify its parameter spa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 159 publications
(211 reference statements)
0
12
0
Order By: Relevance
“…(iii) Supersymmetry frameworks. These include minimal supersymmetric SM (MSSM) [39][40][41], vectorlike extended MSSM [42,43], and the minimal R-symmetric supersymmetric SM (MRSSM) [44]. 3 Among these frameworks, supersymmetry (SUSY) explanations are quite naturally applied to account for Δa μ because they introduce an additional supersymmetric contribution a SUSY μ to a μ , which is generically given as follows [45].…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Supersymmetry frameworks. These include minimal supersymmetric SM (MSSM) [39][40][41], vectorlike extended MSSM [42,43], and the minimal R-symmetric supersymmetric SM (MRSSM) [44]. 3 Among these frameworks, supersymmetry (SUSY) explanations are quite naturally applied to account for Δa μ because they introduce an additional supersymmetric contribution a SUSY μ to a μ , which is generically given as follows [45].…”
Section: Introductionmentioning
confidence: 99%
“…In this case again, the scenario of figure 16 with very large µ is the only option to obtain significant a SUSY µ [174,181,184,224]. We mention that the scenario with µ in the multi-TeV region is also important to obtain large a SUSY µ in the context of various specific model constructions, such as models based on Pati-Salam symmetry [194] (here, at the same time light Winos are preferred), models with usual GUT constraints but extra vectorlike matter fields [200,216], and in a hybrid gauge-gravity mediation model with only four free parameters [206].…”
Section: (Bl)-scenario With Light Sleptons and Binomentioning
confidence: 92%
“…For recent studies in the light of LHC run-II data we refer to refs. [200][201][202][203][204] (which involve a detailed recasting of LHC data) and (which involve model building, the construction of specific scenarios and/or constraints from dark matter or electroweak precision observables). Earlier studies of the SUSY phenomenology of a µ of the LHC run 1 era can be found in refs.…”
Section: Supersymmetry and The Minimal Supersymmetric Standard Modelmentioning
confidence: 99%
“…The results are presented in terms of number of observed events in the 3l + E / T channel in each SR and the corresponding number of SM backgrounds (see Table 13 and 14 of [16]) extracted from the data. With these two numbers one can obtain the model independent upper bound on N BSM for each SR [62]. We have used this information to constrain the pMSSMs discussed in the last section.…”
Section: The Simulationmentioning
confidence: 99%